PENDIDIKAN ISLAM MASA UMAYYAH DAN INDONESIA - Ali Akhbar Abaib Mas Rabbani Lubis (Medina-te : Jurnal Studi Islam, 2020)
This research did not only discussthe aspects of Islamic education that existed during the Umayyad Empire but also touched on the discussion on Islamic education in Indonesia which was related to (formal) institutions. The purpose of this research was to link Islamic education during the Umayyad dynasty with the development, depiction, and implementation of Islamic education in Indonesia. The researcher was based on the continuity aspect as a historical perspective using a linear and cyclic analysis knife as a theoretical framework. The method used was qualitative and the explanation was descriptive analysis. The explanation can be analyzed through several stages, including the stages of data condensation, data display, and conclusion: drawing/verifying. The result of the research found that Islamic education in the Muawiyyah Imperium and Islamic education in Indonesia through its depiction has historical continuity so that the implementation of education in Indonesia was inseparable from how the existing format in Islamic education in the Umayyad Dynasty era.